The Influence of Peer Interaction on The Smoking Behavior of Male Students in Grade IX (Implications for Guidance and Counseling) - Selvianti.A; Fuaddillah Putra; Suryadi (Global Action and Education for Society, 2026)
This research is motivated by the prevalence of smoking behavior in SMP Negeri 1 Tigo Nagari, where some students smoke due to peer influence, such as following others, invitations, or fear of being ostracized. The purpose of this study is to describe: (1) the level of peer interaction, (2) the level of smoking behavior, and (3) the influence of peer interaction and smoking behavior. This study uses a quantitative approach with a simple linear regression test. The study population was 52 male students in grade IX who were sampled using a total sampling technique. Data were collected through a questionnaire instrument, and the data were analyzed using a simple linear regression formula. The results of the study indicate that peer interaction is in the high category and smoking behavior is in the moderately high category, and there is a fairly strong influence between the two. Therefore, it is recommended for guidance and counseling teachers to increase positive peer interaction and reduce smoking behavior with various counseling services with relevant and interesting topics about smoking behavior.